EFFECT OF RED GINGER (Zingiber officinale Rosc. Var Rubrum) ETHANOL EXTRACT OR SILDENAFIL IN LIBIDO: A COMPARATIVE STUDY USING MALE WHITE RATS (Rattus norvegicus) MODEL WITH DIABETES MELLITUS - Hadibrata, Exsa; Sutyarso; Busman, Hendri; Ramdini, Dwi Aulia (Indonesian Urological Association, 2025)
Objective: To compare the effect of red ginger ethanol extract and Sildenafil on increasing the libido of diabetic rat models and determine the dose that significantly affects the increase in libido of diabetic rat models. Materials & Methods: This study is an experimental was conducted on 30 male Sprague dawley white rats divided into 6 groups, namely normal control group, negative control group, sildenafil positive control group, 200 mg ginger group, 400 mg ginger group and 600 mg ginger groupstudy consisting of test animal groups: normal control group; negative control; positive control with sildenafil administration, and treatment groups consisting of: dose I (200mg/kgBB); dose II (400mg/kgBB) and, dose III (600mg/kgBB). All groups except the normal control received alloxan induction at the initial stage of testing. The effect of increasing the libido of rats is seen from sexual activity including: latency of copulation, latency of riding (climbing) and frequency of riding. Results: The results of this study indicate that the administration of red ginger ethanol extract at a dose of 400mg/kgBB or 600mg/kgBB has the same potential as sildenafil in increasing the libido of diabetic rat models. Conclusion: The administration of red ginger ethanol extract at a dose of 400mg/kgBB or 600mg/kgBB has the same potential as sildenafil in increasing the libido of diabetic rat models. Keywords: Red ginger, libido, diabetic rat models.